A prospective, cross-sectional study to establish age-specific reference intervals for neonates and children in the setting of clinical biochemistry, immunology and haematology: the HAPPI Kids study protocol. Issue 4 (3rd April 2019) - Hoq, Monsurul; Karlaftis, Vicky; Mathews, Susan; Burgess, Janet; Donath, Susan M; Carlin, John; Monagle, Paul; Ignjatovic, Vera
Abstract : Introduction: The clinical interpretation of laboratory tests is reliant on reference intervals. However, the accuracy of a reference interval is dependent on the selected reference population, and in paediatrics, the ability of the reference interval to reflect changes associated with growth and age, as well as sex and ethnicity. Differences in reagent formulations, methodologies and analysers can also impact on a reference interval. To date, no direct comparison of reference intervals for common analytes using different analysers in children has been published. The Harmonising Age Pathology Parameters in Kids (HAPPI Kids) study aims to establish age-appropriate reference intervals for commonly used analytes in the routine clinical care of neonates and children, and to determine the feasibility of paediatric reference interval harmonisation by comparing age-appropriate reference intervals in different analysers for multiple analytes. Methods and analysis: The HAPPI Kids study is a prospective cross-sectional study, collecting paediatric blood samples for analysis of commonly requested biochemical, immunological and haematological tests. Venous blood samples are collected from healthy premature neonates (32–36 weeks of gestation), term neonates (from birth to a maximum of 72 hours postbirth) and children aged 30 days to ≤18 years (undergoing minor day surgical procedures). Blood samples are processed according to standard laboratory procedures and, if not processed immediately, stored at –80°C. A minimum of 20 samples is analysed for every analyte for neonates and then each year of age until 18 years. Analytical testing is performed according to the standard operating procedures used for clinical samples. Where possible, sample aliquots from the same patients are analysed for an analyte across multiple commercially available analysers. Ethics and dissemination: The study protocol was approved by The Royal Children's Hospital, Melbourne, Ethics in Human Research Committee (34183 A). The study findings will be published in peer-reviewed journals and shared with clinicians, laboratory scientists and laboratories.